Thwarted Access: Navigating a Way Towards Enhancing Collaboration Between Public Health and Primary Care Practitioners - McCluskey, Hilary June (Auckland University of Technology, 2020)
Many of the most urgent public health difficulties cannot be addressed by single agency interventions (Procter, Brooks, Wilson, Crouchman, & Kendall, 2015; Rawaf et al., 2018; World Health Organization, 2008); instead requiring collaboration across public and private sectors. For the past two decades, the New Zealand Ministry of Health (MoH) (2001, 2011, 2016) and World Health Organization (WHO) (2008, 2014) have directed greater collaboration between primary care and public health. Collaboration strengthens combined skills to expand reach, enhance healthcare delivery, and reduce duplication. However, when this research commenced, there was limited evidence determining how primary care and public health practitioners were collaborating. This research took a qualitative method using grounded theory/grounded action principles and processes to examine how public health and primary care practitioners collaborate, determining what practitioners do to manage any concerns arising, with view to developing an actionable plan to resolve such issues. Phase one explored findings from twenty-one interviews with three general practitioners (GPs), six practice nurses, ten public health nurses and one public health officer, using grounded theory methods of constant comparative analysis, theoretical sampling, theoretical coding and theoretical sensitivity. “Thwarted access” was identified as the main concern, whereby practitioners had difficulty in both gaining access to the other practitioner, and in achieving understanding on ways of working together on client care. “Thwarted access” was mediated by integrating codes of time and geography, knowledge and roles, and power and responsibility. The core category “Clearing the way” represented the way practitioners managed these issues, as practitioners sought to make collaboration work using solution focused methods to try to resolve or move around barriers to collaboration. The category “controlling workflow” portrayed ways practitioners gain access and transmit information, by moving between “managing bombardment”, “channelling information” and “selective knowing”. The category “navigating responsibility” was concerned with what happens once practitioners are collaborating around care, using one of three sub-categories: “assuming responsibility”, “shifting responsibility” or “balancing responsibility”. Phase two involved developing actionable opportunities from the identified concerns and existing resolutions. Due to time constraints presented by the professional doctorate process, the usual final stage of implementing action cycles was omitted from this research. Four actionable categories of “accessing”, “promoting”, “informing” and “collaborating on care” provided resolution for the concerns expressed and formed the basis for the developed action plan. One of the main impediments to collaboration was a lack of knowledge about roles and functions, combined with limited understanding around best ways of working together. There was no collaboration on identifying population issues. Practitioners worked by resolving immediate concerns without considering how more permanence could be developed, with minimal resultant gain in understanding of roles and functions. Significant issues impacting on developing working relationships included structural funding issues and relational power issues between doctors and nurses. Whilst local action may be taken to influence change, implementing national changes encouraging some joint education between doctors and nurses, and changing the pay structure of primary care practices would have a wider impact on collaboration.
Keywords: Collaboration; Public health; Primary care; Integration; Community health; Prevention; Early intervention; Access; Collaborative care